Structure of the granitic pegmatite field of the Northern coast of Portugal—inner pegmatite structures and mineralogical fabrics - Faria, Cristiana (2019)
On the coastline of Northern Portugal, metamorphic formations and pegmatites were the subject of structural analysis with the main goal of understanding Variscan kinematics and related pegmatite intrusion. This study also aims to discriminate, select and characterize relevant aspects of the structure and the paragenesis of pegmatites, well exposed as a result of coastal erosion, justifying its inclusion in the geological heritage of the Northern coast of Portugal. The pegmatite bodies show distinctive internal and external structures that are attributable to different modes of emplacement and subsequent deformation. The pegmatitic implantation in the areas of Moledo and Afife occurs in an intragneissic and perigranitic environment, for the first area, and perigneissic and perigranitic environment, for the second. In Pedras Ruivas predominates the implantation into an exo-gneissic to exo-granitic domain. The Moledo veins show evidence of multiphase open/filling, revealing positions, shapes, attitudes, sizes and internal structures that change as a function of the host lithology and host structure, but mainly due to the dilation and the cycles number of local telescoping. The structural analysis of the pegmatite bodies allows the deduction of a local fulcrum of expansion that hypothetically overlaps a hidden stock of parental granite. In Afife and Pedras Ruivas, some pegmatitic lenses are specialized and mineralized in Li, Cs and Ta, with spodumene and tantalite ± cassiterite. Spodumene occurs as giant crystals, centimetric to pluri-decimetric in length, which mark very clearly the structures of in situ or in flow crystallization inside the pegmatites (primary structures) and also the secondary structures resulting from deformation. The geometric analysis of fabrics helps the individualization of well-defined stages of progressive evolution of the deformation of the pegmatites, allowing its correlation with major D2–D3 episodes of regional Variscan deformation.